Transthoracic versus transhiatal esophagectomy for the treatment of esophagogastric cancer: a meta-analysis - Boshier, Piers R; Anderson, Oliver; Hanna, George B (Annals of surgery, 2011)
To study the differences in short and long-term outcomes of transthoracic and transhiatal esophagectomy for cancer. Studies have compared transthoracic with transhiatal esophagectomy with varying results. Previous systematic reviews (1999, 2001) do not include the latest randomized controlled trials. Systematic review of English-language studies comparing transthoracic with transhiatal esophagectomy up to January 31, 2010. Meta-analysis was used to summate the study outcomes. Methodological and surgical quality of included studies was assessed. Fifty-two studies, comprising 5905 patients (3389 transthoracic and 2516 transhiatal) were included in the analysis. No study met all minimum surgical quality standards. Transthoracic operations took longer and were associated with a significantly longer length of stay. There was no difference in blood loss. The transthoracic group had significantly more respiratory complications, wound infections, and early postoperative mortality, whereas anastomotic leak, anastomotic stricture, and recurrent laryngeal nerve palsy rate was significantly higher in the transhiatal group. Lymph node retrieval was reported in 4 studies and was significantly greater in the transthoracic group by on average 8 lymph nodes. Analysis of 5-year survival showed no significant difference between the groups and was subject to significant heterogeneity. This meta-analysis of studies comparing transthoracic with transhiatal esophagectomy for cancer demonstrates no difference in 5-year survival, however lymphadenectomy and reported surgical quality was suboptimal in both groups and the transthoracic group had significantly more advanced cancer. The finding of equivalent survival should therefore be viewed with caution.